Socialization & Financial Management Training in the Maulidurrasul Reading Organization in Sijono Village - Amalina Zulfa; Hendri Hermawan Adinugraha; Dina Nazilatul Hidayah; Ade Gunawan (Peneliti Teknologi Teknik Indonesia, 2023)
Financial management is everything in the activities of a company or organization that is related to financial governance, how to obtain funds and manage assets according to organizational goals in creating and maintaining organizational value through making the right decisions. Financial management is very much needed in an organization. Financial management in an organization refers to all aspects related to the management and utilization of financial resources owned by the organization. because if an organization does not manage its finances well it will have an impact on the organization itself. So the aim of this service is to socialize and provide training regarding financial management to organizations that regularly recite the Maulidurrasul in Sijono village. The method used in this service is teaching, delivering material, discussions and questions and answers, socialization (counseling), providing training and mentoring to the core management of the organization. The results of this service show that financial management and record keeping in this organization is still very simple, namely only recording the names of participants who attended the birthday reading event and the cash that came in, and some participants had enough good at managing finances, they can organize their finances so that they can be used as optimally as possible.